ANSYS simulation study of MEMS tuning fork gyroscope: article - Abdul Rahman, Muhammad Syafwan (2013)
This paper presents a MEMS based Tuning Fork Gyroscope (TFG) design by using ANSYS software. The designing of the Tuning Fork Gyroscope is based on the architecture and the parameter that been chosen from the previous studies. The structure of TFG is focus on the capacitance at the comb’s structure and the chosen parameter are based on which factor that makes greater effect on the sensing when it is variance and the parameter is using Taguchi method to determine the mathematical formulation of the design of experiments. From the simulation results, it can be conclude that the best design of Tuning Fork Gyroscope based on capacitance which had the values of 260 μm for comb finger length, 30 μm for comb finger width, 80 μm comb finger thickness and lastly capacitance gap of 3 μm.